ToyMatch: a temperament-aligned toy recommendation system for circular design in early childhoods - Halli, Sinem; Kaya, Cigdem; Toreyin, Behcet Ugur (Frontiers in Sustainability, 2025)
IntroductionToy consumption during early childhood presents a critical opportunity to integrate child temperament, sustainable toy design, and value-aligned decision-making into everyday caregiving. Yet most existing recommendation systems focus on age or gender, neglecting emotional durability, caregiver sustainability priorities, and the potential of circular consumption informed by transdisciplinary methods.MethodsThis study introduces ToyMatch, a multi-layered toy recommendation system that integrates psychological profiling (based on the ICID-FFM model), behaviorally defined toy design features, and value-based filters derived from a prior Analytic Hierarchy Process study with 220 caregivers in Türkiye. The system was empirically tested with a separate sample of 214 Turkish caregivers of 3- to 6-year-old children. Clustering, regression, and SHAP-based analyses were conducted to evaluate alignment between temperament traits, design features, and toy preferences.ResultsResults showed meaningful matching patterns for Extraversion, Conscientiousness, and Openness traits, while Agreeableness and Neuroticism remained less predictive.Discussion/conclusionA mobile interface prototype was proposed to operationalize the recommendation process through a low-input, stereotype-neutral structure. Although emotional durability and long-term behavioral impact were not directly measured, the findings suggest that temperament-aligned, value-embedded toy design can promote longer engagement and more sustainable consumption habits. By encouraging developmentally attuned and emotionally resonant toy use, ToyMatch contributes a speculative but actionable model for cultivating circular mindsets in early childhood design and caregiving practices.